2017
DOI: 10.1111/1460-6984.12334
|View full text |Cite
|
Sign up to set email alerts
|

Vocal and gestural productions of 24‐month‐old children with sex chromosome trisomies

Abstract: The study showed the importance of early detection of language risk factors in children with SCT, while also considering the use of compensatory strategies (e.g., the use of communicative gestures).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 44 publications
1
29
1
Order By: Relevance
“…Zampini et al, studied 15 boys and girls with an extra X chromosome at the age of 24 months. Parents from children with an extra X reported that their child produced significantly less words than parents of control children.…”
Section: Resultsmentioning
confidence: 99%
“…Zampini et al, studied 15 boys and girls with an extra X chromosome at the age of 24 months. Parents from children with an extra X reported that their child produced significantly less words than parents of control children.…”
Section: Resultsmentioning
confidence: 99%
“…Communication delays are evident from the first stages of language development (Samango‐Sprouse 2001, Zampini et al . 2018a, 2018b). For instance, Samango‐Sprouse (2001, Samango‐Sprouse and Law 2001) found the presence of a delayed babbling and phonological development in children with Klinefelter syndrome younger than 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…The delay in vocabulary development persists at 24 months: in the study of Zampini et al . (2018b), 75% of males with Klinefelter syndrome and 43% of females with triple X syndrome were late‐talking children (i.e., children with a vocabulary size lower than 50 words at 24 months).…”
Section: Introductionmentioning
confidence: 99%
“…An alteration was noticed in the elaboration of sentences, usually simple, with few elements and syntactic changes concerning the use of verbal tenses, besides pragmatic difficulties. The literature describes that the late development of language and speech may persist beyond childhood, with problems in syntactic production and narrative competence 13,15 . Significant problems were also observed in learning abilities, with deficiencies in all tests applied.…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus in the literature about the intense difficulty in communication in individuals with KS [2][3][4][5][6] . Important deficits in expressive and receptive language were described, as well as alterations in short-term verbal memory, comprehension and utilization of grammar rules, speech-language processing and the literacy process 4,14,15 . Additionally, there are limitations in written expression and arithmetic, being classified into specific learning disorders as dyslexia and dysorthography.…”
Section: Introductionmentioning
confidence: 99%